Hubungan Status Hidrasi, Aktivitas Fisik dengan Kejadian Overweight Pada Mahasiswi Institut Kesehatan Immanuel - Lussy Lussy; Iriyanti Harum; Asysyfa Riana (Jurnal Ilmiah Gizi dan Kesehatan (JIGK), 2026)
Overweight is a global health problem that also affects female university students. This condition may be influenced by hydration status and physical activity. This study aimed to analyze the relationship between these factors and the incidence of overweight among female students at Immanuel Health Institute. A case-control design was applied, involving 92 respondents, comprising 42 overweight individuals and 46 with normal nutritional status. Hydration status was assessed using the PURI (Self-Check Urine) test, physical activity was evaluated with the short version of the IPAQ questionnaire, and nutritional status was determined by calculating BMI. Most overweight respondents were aged 20–25 years (76.1%), underhydrated (80.4%), and had low physical activity levels (67.4%). Chi-square analysis showed a significant association between hydration status (p=0.000; OR=9.397) and physical activity (p=0.000; OR=21.700) with overweight. In conclusion, hydration status and physical activity are significantly associated with overweight. It is recommended that students maintain adequate fluid intake and engage in regular physical activity. Keywords : Overweight, Hydration Status, Physical Activity, Female Students